2019
DOI: 10.1002/1878-0261.12559
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CDK9 for treatment of colorectal cancer

Abstract: Colorectal cancer (CRC) remains one of the most lethal human malignancies, and pursuit of new therapeutic targets for treatment has been a major research focus. Cyclin‐dependent kinase 9 (CDK9), which plays a crucial role in transcription, has emerged as a target for cancer treatment. CDKI‐73, one of the most potent and pharmacologically superior CDK9 inhibitors, has demonstrated excellent anti‐tumour efficacy against several types of cancers. In this study, we evaluated its therapeutic potential against CRC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…To the best of our knowledge, the present study was the first to evaluate the association of CDK9 and tumor-infiltrating CD8 + T cells in MSS CRC. A number of studies have demonstrated that CDK9/P-TEFb is involved in the cell growth and survival of several types of cancer, including CRC (15,49,50). However, these studies have focused on the cancer cells themselves, ignoring the effect of CDK9 on the TME.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, the present study was the first to evaluate the association of CDK9 and tumor-infiltrating CD8 + T cells in MSS CRC. A number of studies have demonstrated that CDK9/P-TEFb is involved in the cell growth and survival of several types of cancer, including CRC (15,49,50). However, these studies have focused on the cancer cells themselves, ignoring the effect of CDK9 on the TME.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin-dependent kinase 9 (CDK9) is a key regulator of transcriptional elongation, which is a promising therapeutic target in cancer, particularly for types of cancer driven by transcriptional dysregulation (13,14). However, the mechanism and clinical transformation of CDK9 in CRC have been rarely reported (15). In addition, it has been demonstrated that APC/BRAF/SMAD4 gene mutations lead to upregulation of transcription, which leads to the occurrence and development of CRC (1618).…”
Section: Introductionmentioning
confidence: 99%
“…There are some MNK1/2 inhibitors tested in CRC, such as cercosporamide, which suppresses eIF4E phosphorylation in colon cancer cell lines blocking the growth of HCT116 colon carcinoma xenograft tumors [77]; 6-hydroxy-4-methoxy-3-methylbenzofuran-7-carboxamide derivatives compounds 5o and 8k, that also exhibit anti-proliferative activity and block eIF4E phosphorylation in the CRC HCT-116 cell line [82]; 42i, a pyridine-aminal derivative synthesized as MNK1/2 inhibitor that significantly blocks eIF4E phosphorylation in colon cancer CT-26 cell line and inhibits tumor growth in CT-26 allograft model [83] and 4t, a pyridine derivative with anti-proliferative activity against CRC cell lines among others [98]. Targeting different proteins than MNKs, two compounds are found to downregulate MNK1 in CRC, CDKI-73 [142] and metformin [143]. Regarding MNK inhibitors in clinical trials, the MNK1/2 inhibitor eFT508 is being evaluated in phase II in colorectal cancer patients alone or in combination with Avelumab.…”
Section: Mnk In Gastrointestinal Cancermentioning
confidence: 99%
“…Cyclin-dependent kinases (CDKs) are such potential biomarkers for the diagnosis of CRC due to their crucial role in the elongation step of the global transcription process [ 2 ]. CDKs and their specific functions in cancer have been comprehensively investigated; they are involved in regulation of the cell cycle by interacting with specific cell-cycle–regulatory cyclins [ 3 ].…”
Section: Introductionmentioning
confidence: 99%